2012 annual report, precursors report, narcotic drugs, psychotropic substances : guidelines - report on the availability of internationally controlled drugs (UN New YorkUS, 2013)
Describes the evolution and achievements of shared responsibility in drug control. Presents examples of good practice in applying the principle of shared responsibility to drug control efforts in areas such a demand reduction, supply reduction, judicial cooperation and the control of licit trade in drugs.
Keywords: NARCOTICS